wz

Výrazy (sčítání, odčítání, roznásobování, vytýkání)       

 

 

1.      Zjednoduš výrazy:

 

       a) 9u - (3u - 6) =                                                   b) (c+1) - 3c + 4 + (-5c+4) =

 

       c) (0,6z - 5x + y) - (0,5z + 2,5z - y) =                  d) (15r - 4s) - [ 7r - ( - r + s )] - 3 =      

 

       e) (a - 1) - (a - 2) - (a - 3) - (a - 4) =                      f) - 4 - [ - (2a - 1) + (5 - 3a) - 5 ] + 1 =     

 

       g) 5a + { 3b + [ 6c - 2a - (a - c) ] } - [ 9a - (7b + c) ] =

 

 

2.      Zjednoduš výrazy nejprve jejich roznásobením a pak dále zjednoduš:

 

       a)     - 5s . (2s + 3)=           b)  ( 8a – 4 ) . ( 3a + 6 ) =           c)   - 2 . (x - 1) - 2 . (1 - x) =

 

       d)     - 3a . (a - 3) - 4 . (3 - a) =            e)  9a ( 2a – 3b ) =

 

3.      Zjednoduš výrazy:

 

       a) ( 7x – 8y + z ) -  ( 3x + 5y – z ) =                             b) -2 - 4a + (3a + 1) + 3a + (a - 2) =

 

       c) ( -11x + 4,5y - 8z) - ( 0,5z - 18z + 9y) =                  d) -5y - [ - 8x + 3y - (y + x) + 9 ] =      

 

       e) -2a - ( -5a - 1) - (2a - 2) - 1 =                         f) 7x + 3y - [ 5x + 8y + (9x + 5y) ] + 6x =     

 

       g) 4m - 2n - { 5m - [ 8n - (m + n) ] + ( 3n - 10m) } =                h) 3x - (5 - 2x) =

      

       h)  ( 5a – 6b + c ) – ( 3a + b – c ) =                              

 

 

4.      Zjednoduš výrazy nejprve jejich roznásobením a pak dále zjednoduš:

 

       a)    3u . ( -2u + 3)                                                            b)  -3 . (1 - x) - 3 . (x - 1) =

 

       c)  -3u . (2 - u) - 3 . (u2 - 2u + 1) =      d)  6x . ( 2x – 3y ) =      e)  ( 7x – 3 ) . ( 5x + 2 ) =

 

5.      Vynásob:

a)      ( 5z + 4 ) . ( 4z – 2 ) =                                               ( 3a + 5 ) . ( a – 2 ) =

 

6.      Vypočítej:

 

a)   -2 . ( 3x - y + 2 ) =                               b)            ( 2a - 1 ) . ( a - 2 ) - ( a - 1 ) . ( 3a + 1 ) =